2023
DOI: 10.1097/sih.0000000000000738
|View full text |Cite
|
Sign up to set email alerts
|

Two Affordable, High-Fidelity Central Venous Models for Ultrasound-Guided Interventional Training

Abstract: Introduction Ultrasound-guided vascular access is an increasingly popular technique due to its reduced complication and higher success rates. Commercially bought training phantoms allow providers to develop tactile skills in a low-risk setting, but are also expensive and poorly accessible. This study analyzes the efficacy of homemade, low-cost, gelatin-based central line vascular models to teach vascular anatomy and intravascular access techniques in training physicians. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…Although Tuzer et al 32 found that the standard patient model was more effective than HFS in improving students' knowledge of chest and heart examinations, more reports have indicated that using HFS in medical education can more effectively enhance operational proficiency, improve professional skills, and reduce patient risk, [33][34][35] consistent with the results of this study. This may be because HFS provides nursing students with the opportunity to practice and repeat technical operations in a safe environment.…”
Section: Discussionsupporting
confidence: 86%
“…Although Tuzer et al 32 found that the standard patient model was more effective than HFS in improving students' knowledge of chest and heart examinations, more reports have indicated that using HFS in medical education can more effectively enhance operational proficiency, improve professional skills, and reduce patient risk, [33][34][35] consistent with the results of this study. This may be because HFS provides nursing students with the opportunity to practice and repeat technical operations in a safe environment.…”
Section: Discussionsupporting
confidence: 86%